Role of innovation in economic growth in a New Zealand context - Little, Struan (New Zealand Science Review, 2011)
​I’m going to be talking, essentially, about two things: first that innovation is profoundly important for New Zealand’s economic performance and growth and, secondly, that to gain greater economic dividends from science, research and innovation, we need to get much more fusion and synergy between our scientists and firms.